Basolateral Amygdala to Nucleus Accumbens Communication Differentially Mediates Devaluation Sensitivity of Sign- and Goal-Tracking Rats - Kochli, Daniel E.; Keefer, Sara E.; Gyawali, Utsav; Calu, Donna J. (Frontiers in Behavioral Neuroscience, 2020)
Rats rely on communication between basolateral amygdala (BLA) and nucleus accumbens (NAc) to express lever directed approach in a Pavlovian lever autoshaping (PLA) task that distinguishes sign- and goal-tracking rats. During PLA, sign-tracking rats preferentially approach an insertable lever cue, while goal-tracking rats approach a food cup where rewards are delivered. While sign-tracking rats inflexibly respond to cues even after the associated reward is devalued, goal-tracking rats flexibly reduce responding to cues during outcome devaluation. Here, we sought to determine whether BLA-NAc communication, which is necessary for sign, but not goal-tracking, drives rigid appetitive approach of sign-tracking rats that are insensitive to manipulations of outcome value. Using a contralateral chemogenetic inactivation design, we injected contralateral BLA and NAc core with inhibitory DREADD (hm4Di-mCherry) or control (mCherry) constructs. To determine sign- and goal-tracking groups, we trained rats in five PLA sessions in which brief lever insertion predicts food pellet delivery. We sated rats on training pellets (devalued condition) or chow (valued condition) prior to systemic clozapine injections (0.1 mg/kg) to inactivate BLA and contralateral NAc during two outcome devaluation probe tests, in which we measured lever and foodcup approach. Contralateral BLA-NAc chemogenetic inactivation promoted flexible lever approach in sign-tracking rats, but disrupted flexible food-cup approach in goal-tracking rats. Consistent with a prior BLA-NAc disconnection lesion study, we find contralateral chemogenetic inactivation of BLA and NAc core reduces lever, but not foodcup approach in PLA. Together these findings suggest rigid appetitive associative encoding in BLA-NAc of sign-tracking rats hinders the expression of flexible behavior when outcome value changes.